IDEAL PRIMA FUZZY DI SEMIGRUP S - Abdurahim Abdurahim (Universitas Muhammadiyah Ponorogo, 2017)
A fuzzy membership function is a function that maps the nonempty set to a closed interval . Furthermore, if the function domain is replaced with a semigroup, then the function is called fuzzy subset. A fuzzy subset mapping to is denoted by . A fuzzy subset is called fuzzy ideal if it satisfies both and . Moreover, is called a fuzzy prime ideal if for any fuzzy ideal and , with implies or . In this paper be investigated about some characteristics of prime fuzzy ideals and some example of them.